2016
DOI: 10.1242/dev.129098
|View full text |Cite
|
Sign up to set email alerts
|

NRPB3, the third largest subunit of RNA polymerase II, is essential for stomatal patterning and differentiation inArabidopsis

Abstract: Stomata are highly specialized epidermal structures that control transpiration and gas exchange between plants and the environment. Signal networks underlying stomatal development have been previously uncovered but much less is known about how signals involved in stomatal development are transmitted to RNA polymerase II (Pol II or RPB), which plays a central role in the transcription of mRNA coding genes. Here, we identify a partial loss-of-function mutation of the third largest subunit of nuclear DNA-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 69 publications
(83 reference statements)
3
26
0
1
Order By: Relevance
“…Among the transcriptional co-regulators we found two significantly enriched transcriptional co-activators: MED16, which is part of the mediator complex that links TFs to RNA Pol II (Kidd et al 2011), and HAC1, which is a histone acetyl transferase (HAT) (Deng et al 2007). Combined with previous data showing a link between FAMA and RNA Pol II (Chen et al 2016), this suggests that FAMA activates genes both directly by recruiting RNA Pol II and by opening up the chromatin for other transcriptional regulators. Among transcriptional co-repressors were TOPLESS (TPL)-related proteins TPR3 and TPR4 and LEUNIG (LUG) and LEUNIG HOMOLOG (LUH), which recruit histone deacetylases (HDACs) to TFs (Long et al 2006).…”
Section: Figure 5: 'Fama Interactome' Experiments -Pl With Tid Revealssupporting
confidence: 70%
See 1 more Smart Citation
“…Among the transcriptional co-regulators we found two significantly enriched transcriptional co-activators: MED16, which is part of the mediator complex that links TFs to RNA Pol II (Kidd et al 2011), and HAC1, which is a histone acetyl transferase (HAT) (Deng et al 2007). Combined with previous data showing a link between FAMA and RNA Pol II (Chen et al 2016), this suggests that FAMA activates genes both directly by recruiting RNA Pol II and by opening up the chromatin for other transcriptional regulators. Among transcriptional co-repressors were TOPLESS (TPL)-related proteins TPR3 and TPR4 and LEUNIG (LUG) and LEUNIG HOMOLOG (LUH), which recruit histone deacetylases (HDACs) to TFs (Long et al 2006).…”
Section: Figure 5: 'Fama Interactome' Experiments -Pl With Tid Revealssupporting
confidence: 70%
“…The low abundance of FAMA and FAMAexpressing cells renders identification of interaction partners and cell type-specific nuclear proteins by traditional methods challenging and makes it well suited for a proof-of-concept experiment. Potential FAMA interaction partners were previously identified in yeast-2-hybrid (Y2H) and bimolecular fluorescence complementation studies (Chen et al 2016;Kanaoka et al 2008;Lee, Lucas, and Sack 2014;Li, Yang, and Chen 2018;Matos et al 2014;Ohashi-Ito and Bergmann 2006), but only few have been confirmed by in vivo functional data.…”
Section: Testing Turboid's Potential To Identify Partners Of a Very Lmentioning
confidence: 99%
“…Some of these marker genes could potentially be involved in regulating the development of stomatal lineage cells. SLAC1 and SCAP1(DOF5.7) play important roles in regulating the development of stomatal lineage cells (Engineer et al, 2015; Chen et al, 2016). Consistently, a high level of expression of SLAC1 and DOF5.7 was detected in YGC and GMC (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The GUS staining assay was performed as previously described (Chen et al, 2016) with T3 ProB1L:GUS transgenic plants of 1-day-old seedlings, 2-day-old seedlings, 10-day-old seedlings, and 8-week-old mature plants. After staining, the samples were rinsed with acetic acid/methanol [1:3 (v/v)].…”
Section: Methodsmentioning
confidence: 99%